2019
DOI: 10.1155/2019/3720308
|View full text |Cite
|
Sign up to set email alerts
|

A Reversible Spectrophotometric Method Based on a Coupled Microfluidic Chip for Highly Selective Ammonium Detection

Abstract: A coupled chip aiming at economical and highly selective ammonium detection was fabricated. It consisted of a reaction chip, a gas-diffusion chip, and a detection chip. Zinc tetraphenylporphyrin dyed on the cation-exchange resin microbeads was used as the indicating material to avoid excess consumption for its reversibility. PDMS was selected as the material of the gas-diffusion membrane. A portable spectrometer was applied for spectrum analysis. By analysis of spectrum change, the high selectivity was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Microfluidics also opens possibilities for designing different serially connected microfluidic chips, for performing different steps automatically in the process of selective ammonia detection from complex aqueous solutions. Zhou et al [ 287 ] demonstrated this approach by converting ammonium ions to gaseous ammonia though a reaction with a strong base within the reaction chip, followed by selective ammonia diffusion within a gas diffusion chip to a separate microfluidic channel, which subsequently leads to optical ammonia detection through a reversible reaction with Zn-tetraphenylporphyrin in a separate detection chip. The authors used PDMS to construct a gas diffusion membrane, though other materials such as polypropylene [ 288 ], polytetrafluoroethylene [ 289 ] or polyvinylidene fluoride [ 290 ] can be applied for ammonia diffusion as well.…”
Section: Sensorsmentioning
confidence: 99%
“…Microfluidics also opens possibilities for designing different serially connected microfluidic chips, for performing different steps automatically in the process of selective ammonia detection from complex aqueous solutions. Zhou et al [ 287 ] demonstrated this approach by converting ammonium ions to gaseous ammonia though a reaction with a strong base within the reaction chip, followed by selective ammonia diffusion within a gas diffusion chip to a separate microfluidic channel, which subsequently leads to optical ammonia detection through a reversible reaction with Zn-tetraphenylporphyrin in a separate detection chip. The authors used PDMS to construct a gas diffusion membrane, though other materials such as polypropylene [ 288 ], polytetrafluoroethylene [ 289 ] or polyvinylidene fluoride [ 290 ] can be applied for ammonia diffusion as well.…”
Section: Sensorsmentioning
confidence: 99%